Use of scratchcards for allocation concealment in a prehospital randomised controlled trial. Issue 11 (12th September 2018) - Keen, Leigh; Bulger, Jenna Katherine; Rees, Nigel; Snooks, Helen; Fegan, Greg; Ford, Simon; Evans, Bridie Angela; Longo, Mirella
Abstract : Background: Rapid Analgesia for Prehospital Hip Disruption was a small study designed to determine the feasibility of undertaking a randomised controlled trial (RCT) to test the clinical and cost-effectiveness of paramedics administering Fascia Iliaca Compartment Block as early prehospital pain relief to patients with a fractured hip. The objective was to devise a simple and effective method of random allocation concealment suitable for use by paramedics while in the emergency prehospital setting. Methods: Scratchcards were produced using scratch-off silver stickers which concealed the trial arm allocation. Paramedics were each allocated a unique range of consecutive numbers, used as both the scratchcard number and the patient's study ID. The cards were designed to allow the paramedic to write on the incident number, date and signature. A small envelope holding the cards was prepared for each paramedic. The study took place between 28 June 2016 and 31 July 2017 in the Swansea area. Results: Nineteen trial paramedics used 71 scratchcards throughout the study and reported no problems randomly allocating patients using the scratchcards. Five protocol deviations were reported in relation to scratchcard use. On auditing the scratchcards, all unused cards were located, and no evidence of tampering with the silver panel was found. Conclusion: Paramedics can use scratchcards as a method of randomly allocating patients in trials in prehospital care. In the future, a method that allows only the top card to be selected and a more protective method of storing the cards should be used. Scratchcards can be considered for wider use in RCTs in the emergency prehospital setting. Trial registration number: ISRCTN60065373 ; Post-results.